Akibat Hukum Pengangkatan Anak terhadap Hak Mewarisi Melalui Penetapan Pengadilan Agama No. 57/Pdt.P/2019/PA.Lpk - Noval Pra Ashari; Hasim Purba; Rosnidar Sembiring; Maria Kaban (Jurnal Hukum Lex Generalis, 2025)
Abstract Child adoption is a practice that has long been carried out by Indonesian society, generally by married couples who do not yet have children, and is implemented in accordance with customs and laws and regulations. This normative legal research with descriptive analytical nature examines the legal system of child adoption, court validation, and the legal consequences arising using statutory, conceptual, and case approaches with qualitative analysis. The research results show fundamental differences between customary legal systems that sever blood relations between adopted children and biological parents, Islamic law and Law No. 35 of 2014 which do not sever such lineage relations. Child adoption requirements are regulated in Government Regulation No. 54 of 2007 and Social Affairs Minister Regulation No. 110/HUK/2009, where applications are submitted through social institutions then to the court to obtain a court decree if the specified requirements are met. The legal consequences of child adoption through court decisions show that adoptive parents only replace the role of biological parents in caring for, educating, and nurturing without severing blood relations, so that according to the Compilation of Islamic Law (KHI), adopted children are not included as heirs of adoptive parents but are entitled to obligatory bequests according to Article 209 paragraph (2), adoptive parents cannot become marriage guardians for adopted daughters and are not entitled to inherit from each other but may obtain obligatory bequests based on Article 209 paragraph (1), while adopted children still have blood relations with their biological parents and are entitled to inherit from each other according to the provisions of Articles 176-193 KHI.